Data Visualization of Lecturer of Digital Business Study Program Darmajaya Institute of Informatics and Business - Diki Andita Kusuma; Ratna Nurhaya; Mukhas Munif Ahsani; M S Hasibuan (Proceeding International Conference on Information Technology and Business, 2021)
Digital Business Study Program is a study program that was born in 2019 from the Faculty of Economics at the Darmajaya Institute of Informatics and Business (IIBDarmajaya). This study program is the most favorite study program at FEB IIB Darmajaya, which of course must be balanced with the many researches carried out by lecturers and students. The efforts of the Darmajaya Institute of Informatics and Business (IIB) to improve the research culture certainly have a very positive impact on the Institute and researchers. Data related to research conducted by lecturerswho are currently presented separately on several websites such as Scopus, Web of Science (WOS) and Google Scholar will make it difficult for various parties who want to use data related to these studies for various purposes. . With the development of Digital Business Studies program, the more research done, so there should be a system that can handle them.Data studio is a tool used to create data visualizations.Therefore, it is very important for the digital business study program to have a system that stores data or information about lecturers in the digital business study program which is presented in the form of data visualization so that the information can be understood in a faster and shorter time because the information is packaged in a variety of formats. Diagrams with attractive colors and shapes. Keywords-Data Visualization, IIB Darmajaya, Data Processing, Data Analytics.